Implementasi Program Pelatihan Keahlian Kerja Tekstil (Textile Training) dalam meningkatkan Kinerja Karyawan PT. Indorama Teknologies Complex Kabupaten Purwakarta Kecamatan Campaka Jawa Barat - Rihanah, Ana; Suherman, Suherman; Siregar, Herlina Herlina (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to describe the implementation of the implementation of textile work skills training program on employee performance at PT. Indorama Teknologies Complex, Purwakarta Regency, Campaka District, West Java. This study uses Qualitative Descriptive. The subjects of this study include HRD PT. Indorama Teknologies Complex, Personnel Staff, Trainers, and Employees of PT. Indorama Teknologies Complex. This research instrument is assisted by observation, interview, and documentation guidelines. Then the researcher's data collection uses observation, interviews, and documentation. The results of the study show that (1) The implementation of textile work skills training is quite good, but it is still a little difficult to eval__uate due to personal reasons and laziness (2) For employee performance at PT. Indorama Teknologies Complex is quite good, but some new employees have a little difficulty adapting to the environment, therefore a deeper approach is needed so that they feel comfortable in the company (3) At the implementation stage, the Process is quite good, because the material and training model are easy to understand with various prizes if anyone can explain in more detail, but their memory is quite lacking, so an eval__uation is needed the next morning to remember yesterday's material (4) In the Product eval__uation, it is quite good because participants can master the material and training model presented, but it is a little difficult to eval__uate training for old employees for certain reasons and laziness, then the company lacks assertiveness, this can affect employee performance in the future, therefore assertiveness is needed for employees to conduct eval__uations. The results of the implementation of textile work skills training as a whole are quite good, but there are still some improvements related to the implementation of training in order to produce the quality and quantity of competent and professional employees.